2013
DOI: 10.1080/01904167.2013.799190
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Chlorophyll Meter (Spad-502) Reading by Specific Leaf Area for Estimating Leaf Nitrogen Concentration in Sweet Sorghum

Abstract: The chlorophyll meter (SPAD-502) is used to estimate nitrogen status of various crops. However, the relationship between SPAD readings and leaf nitrogen concentration (LNC) in sweet sorghum (Sorghum bicolor) has not been fully established. We examined the relationship between SPAD readings and LNC in sweet sorghum in a two-year study; and the effects of leaf thickness on the relationship was also examined. There was a significant relationship between the SPAD reading and LNC at each of two growth stages, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…3, Table 3) and the leaf N concentration in sweet sorghum 31 was used as an indicator to decide the timing of fertilizer topdressing for satisfying the crop demand for N and minimizing N loss in the crop cultivation systems 5,32 . In the present study, it was difficult to define a fixed SPAD reading for the timing of fertilizer topdressing due to the different trends in SPAD readings during the growing seasons in both years (Fig.…”
Section: Effect Of N Input On Sweet Sorghum Productivitymentioning
confidence: 99%
“…3, Table 3) and the leaf N concentration in sweet sorghum 31 was used as an indicator to decide the timing of fertilizer topdressing for satisfying the crop demand for N and minimizing N loss in the crop cultivation systems 5,32 . In the present study, it was difficult to define a fixed SPAD reading for the timing of fertilizer topdressing due to the different trends in SPAD readings during the growing seasons in both years (Fig.…”
Section: Effect Of N Input On Sweet Sorghum Productivitymentioning
confidence: 99%
“…The failure of chlorophyll sensors to distinguish within the range of over-fertilized plants has been observed since the early studies with SPAD-502 chlorophyll meter (Schepers et al 1992;Blackmer and Schepers, 1994). Since then, the results have varied between obtaining significant linear relationships between SPAD-readings and leaf N concentrations (Uchino et al 2013;Mahajan et al 2014; Basyouni, Dunn, and Goad 2015) and their absence (Sibley et al 1996;Bullock and Anderson, 1998;Hardin et al 2012). This discrepancy in results might be due to differences in the nutritional status of the plants in each of the experiments in which the device was used.…”
Section: Journal Of Plant Nutrition 267mentioning
confidence: 98%
“…The SPAD-502 chlorophyll meter (Minolta Camera Co. Ltd., Japan), which measures the transmittance of light through the leaf, has been widely used. Several studies have shown a significant linear relationship between SPAD-readings and laboratory determination of leaf chlorophyll concentration (Hawkins, Gardiner, and Comer 2009;Ruiz-Espinosa et al 2010;Ibrahim and Jaafar 2013) and between SPAD-readings and leaf N concentration (Ibrahim and Jaafar 2013;Uchino et al 2013;Mahajan et al 2014;Basyouni, Dunn, and Goad 2015). The FieldScout CM 1000 meter, more recently manufactured, evaluates by remote sensing the chlorophyll content in the leaves based on the chlorophyll reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…The light at 650 nm is associated with chlorophyll activity (645 and 663 nm), while the other at 940 nm is used to compensate differences in leaf moisture and thickness (Hardin et al, 2012;Raymond Hunt;Daughtry, 2014). The output of these two values is the chlorophyll index (CI), a dimensionless value that has been highly correlated with leaf chlorophyll and nitrogen content for several crops (Martins et al, 2020;Taskos et al, 2015;Duchino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%